EVALUATION OF THREE RUBELLA VACCINES IN CONFERRING PROTECTION - K. Naficy; R. Nategh; M. Khakpour; M. Mohagheghpour; N. Sabouri (Tehran University of Medical Sciences, 1974)
The effeminacy of three rubella vaccines, HPV/77 IDE-5, Cendehill-51 and Wistar RA/27/3 in conferring immunity against untenanted rubella virus was compared. Vaccination resulted in 90-100 percent protection against clinical rubella. Intranasal challenge with the untenanted strain of rubella virus resulted in serologic evidence of in apparent reinfection in three of the ten Cendehill-51 vaccines the virus was isolated from the throat specimens of two, and one developed adenopathy. Two of the eleven RA/27/3 vaccines became reinfected. Virus was isolated from the throat specimen of one and a booster response occurred in that other; the latter developed rash. All of the HPV/177/DE-5 vaccines remained symptom less after the challenge. None demonstrated booster response and shed virus.